Successful management of aspiration pneumopathy without antimicrobial agents: 14 dogs (2014‐2021). (23rd August 2021) - Cook, S.; Greensmith, T.; Humm, K.
Abstract : Objectives: To describe clinical cases of aspiration pneumonitis and pneumonia in dogs, which were successfully managed without antimicrobials. Materials and Methods: Retrospective case review of dogs presenting to a referral teaching hospital between February 2014 and February 2021. Cases were included when a clinical diagnosis of aspiration pneumopathy was made (requiring one or more of the following: radiographic evidence of an aspiration pneumopathy, endotracheal airway sampling consistent with aspiration and/or a positive endotracheal airway sample culture) which was not treated with antimicrobial therapy. Results: Fourteen cases were identified of which nine had respiratory signs including increased respiratory rate or effort (n=8), arterial hypoxaemia (n=2), or a clinician‐determined requirement for oxygen therapy (n=4). Where haematology was performed, five of nine displayed a normal neutrophil count with toxic changes, three displayed neutrophilia and one displayed neutropenia with toxic changes. Endotracheal airway sample cytology in four cases revealed neutrophilic inflammation with bacteria, plant material, yeasts and unidentified foreign material. Where respiratory signs were present, these resolved within 12 to 36 hours. Clinical Significance: In this case series, immunocompetent dogs sustaining aspiration events, even with classical evidence of pneumonitis or pneumonia, have been managed successfully without antimicrobials. Radiography alone cannot be used to determine the requirement for antimicrobials. Better characterisation of the pathogenesis and clinical trajectory of aspiration pneumopathy is required, which may enable a reduction in inappropriate antimicrobial prescriptions.